Monitoring the response of Saudi Arabia's largest fossil aquifer system to climate variability - Abdullah Othman (Journal of Taibah University for Science)
The study utilizes an integrated approach that involves GRACE and Global Precipitation Climatology Project (GPCP) data to analyze temporal water mass variations in Saudi Arabia (KSA). Recently, KSA has witnessed a historic wet period between 2018 and 2020 (i.e., 120–150 mm/year) following a prolonged dry period between 2002 and 2017 (i.e., 80–100 mm/year). Inspection of GRACE data showed a decline in groundwater recharge of −4 to −6 mm during the dry period. The depletion was reduced by 1 to 6.8 mm in the Northeastern side of KSA (e.g. Hail, Al-Jouf, Al-Hudud Ash-Shamaliyah areas) during the wet period. This impressive recovery has led to a groundwater recharge increase of 360 km3 in Hail, 174 km3 in Al-Jouf and 97 km3 in Al-Hudud Ash-Shamaliyah. The findings emphasize the notion that climate change will bring more frequent extreme climatic events to the Kingdom of Saudi Arabia and call for continuous monitoring of aquifers every year.